Hemodynamics and Blood Coagulation System in Patients Operated Following Ulcer Disease Hemorrhagia - V. V. Filatov; V. T. Dolgikh (Общая реаниматология)
Objective: to evaluate the clinical efficacy of hypoxen and nutrients used in the combination therapy of patients operated for bleeding gastroduodenal ulcer. Subjects and methods. Seventy-four patients were examined and treated. All the patients were divided into 3 groups: 1) standard therapy + hypoxen in a daily dose of 1 g for a week; 2) standard therapy + hypox-en and nutrients; 3) standard therapy only. Hypoxen and nutrients were administered on postoperative day 1 via an enter-al feeding tube. Systemic hemodynamic and hemostatic parameters were determined using MICAR-RHEO hardware-software rheographic unit APG2-01 analyzer, respectively. Results. It was established that the hyper- and eukinetic hemodynamic types were predominant before surgery and the eukinetic type was prevalent in the early postoperative period. Hypoxen and nutrients were observed to positively affect central hemodynamic parameters, such as blood pressure, cardiac output, circulating blood volume, and heart rate. Hypercoagulation changes (shorter blood clotting time in a study group and elevated serum fibrinogen levels in a comparison group) on postoperative day 10 suggest that the hemostatic parameters should be monitored and corrected as soon as possible. Key words: ulcer disease, hypoxen, nutritional support, blood circulation, hemostatic system.